Directive Speech Act Translation in ‘Alephia 2053’ Movie Subtitle: Comparison of Arabic-English and Arabic-Indonesian Translation - Irianti, Waviq Alfiana; Anis, Muhammad Yunus (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2024)
This study aims to describe the types of directive speech acts, the use of techniques, translation, methods and ideology of Arabic-English and Arabic-Indonesian translation of 'Alephia 2053' movie subtitles. This research used descriptive analysis to describe the findings qualitative was chosen as the method of this research. Consequently, the data were analyzed using Miles and Huberman and Spradley models. The results of this study stated that there were 80 data consisting of eight types of directive speech acts, in which the frequency of the use of Arabic-English version techniques was found 194 times for 12 techniques. The results of the method and ideology of the Arabic-English version oriented to the target language amounted to 181 data (93.3%) of translation techniques and the translation ideology of the Arabic-English version of directive speech acts adheres to the ideology of domestication. While the frequency of use of the Arabic-Indonesian version of the technique was found 138 times for 11 techniques. The results of the method and ideology of the Arabic-Indonesian version oriented to the target language amounted to 130 data (94.2%) of translation techniques and the ideology of translation of directive speech acts in the Arabic-Indonesian version adheres to the ideology of domestication